Genetic polymorphisms of human cytochrome P450 CYP1A1 in an Egyptian population and tobacco-induced lung cancer. (December 2017) - Ezzeldin, Nada; El-Lebedy, Dalia; Darwish, Amira; El-Bastawisy, Ahmed; Hassan, Mirhane; Abd El-Aziz, Shereen; Abdel-Hamid, Mohamed; Saad-Hussein, Amal
Abstract Background Cytochrome P450 CYP1A1 helps detoxify the potential carcinogens in tobacco smoke, it was reported that polymorphisms in the coding gene result in variation in the expression and activity levels which alter metabolism and clearance of carcinogens and therefore modify cancer risk. In this work, we aimed to identifyCYP1A1 gene polymorphisms associated with lung cancer in Egyptian population and to examine the interaction effect with Tobacco smoking in modulating disease risk. Methods A case–control study was conducted on 150 unrelated lung cancer patients and 150 unrelated control subjects. Genomic DNA was extracted and sequencing analysis ofCYP1A1 gene was performed on ABI PRISM 3100 genetic analyzer. Results Three variants inCYP1A1 gene were identified in heterozygous forms in lung cancer patientsI462V, T461N andI286T . A combined variantT461N/ I462V associated with lung cancer and those who carried this variant were 2-times more likely to develop lung cancer (OR = 2.03, 95% CI = 1.81-2.29, P = 0.04), specially the non-small cell type (NSCLC) (OR = 2.20, 95% CI = 1.93–2.50, P = 0.02). Wild type was more frequent among smoker controls (83.3%) compared to smoker lung cancer patients (54.8%), P = 0.03. Association studies to examine the interaction effect of identified variants with Tobacco smoking in modulating disease risk showed no significant associations. Identified polymorphisms showed no significant implication on the stage or the prognosis of the disease. Conclusion Our findings support thatCYP1A1 polymorphisms play a role in the pathogenesis of lung cancer. In Egyptian population, CYP1A1 I462V, T461N and I286T variants were identified among lung cancer patients and combinedT461N/ I462V was a risk variant for NSCLC in non smokers.